Optic Disc Oedema: Presentation and Causes at a Tertiary Centre in North Karnataka - Raghavendra Ijeri; R.C. Jyoti (Delhi Journal of Ophthalmology)
Aim:- Optic disc oedema is one of the important fundus findings seen in the eye. Many a times, it indicates a systemic pathology. In this study, we try to evaluate various causes of optic disc oedema and their presentation. Materials & Methods:- This observational study was conducted at a tertiary hospital in North Karnataka. This study was conducted from June 2015 to May 2017. Detailed ocular examination including visual acuity, slitlamp examination, detailed fundus evaluation using indirect ophthalmoscope and 90 Diopter lens, and fundus photography was done. Other investigations like blood examination, Visual field analysis and radiological investigations like Computed Tomography scans and Magnetic Resonance Imaging were done when required. Results:- A total of 43 consecutive cases with optic disc oedema were enrolled in this study. Twenty were females and twenty three were males. Out of the 43 cases, 15 cases had papilloedema, 20 cases had optic neuritis, one had anterior ischemic optic neuropathy (AION), 2 had diabetic papillopathy, 2 had Vogt Koyanagi Harada Syndrome (VKH), one had hemiretinal vein occlusion and 2 cases had neuroretinitis. A total of 34.9% patients had papilloedema, 46.5% had optic neuritis, 4.6% each had neuroretinitis, VKH and diabetic papillopathy, and 2.3% each had AION and hemi-retinal vein occlusion. Conclusions:- Optic neuritis was the commonest cause, followed by papilloedema, leading to optic disc oedema.